Ethnomathematics-Based Evaluation Instrument to Measure Students’ Problem-Solving Ability - Maridsha Zalianti; Kamid Kamid; Khairul Anwar (MASI Mandiri Edukasi, 2026)
This study aims to develop an evaluation instrument to assess students’ mathematical problem-solving abilities in an ethnomathematics context, focusing on polyhedra (three-dimensional shapes with flat faces). The research employed a development methodology based on the ADDIE model and involved 29 ninth-grade students. The Analysis phase included identifying needs, reviewing the curriculum, examining student characteristics, and determining learning objectives. In the Design phase, the instrument was constructed by integrating relevant elements of ethnomathematics. The Development phase consisted of expert validation by material and evaluation specialists, followed by individual and small-group trials. The Implementation phase involved a large-group field test, while the Evaluation phase was carried out throughout all stages of the process. The results indicate that the developed instrument is valid (average expert validation score: 85.52%), practical (practicality score: 89%), and effective (effectiveness score: 86.6%). Therefore, the ethnomathematics-based evaluation instrument is effective for assessing students’ mathematical problem-solving abilities during the learning process.